DEVELOPMENT OF INFORMATION AND COMMUNICATION NEEDS OF ENGINEERING STUDENTS - Добровольська, Л.А. (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2013)
In the article are taken up questions of information needs of students, their social conditionality and motivational range of informational needs is specified; importance of inclusion in the number of criteria of efficiency of mass-media of their role in satisfaction and development of information needs of students is confirmed.